A Peer Counselling Model for Computer-Assisted Career Counselling - France, Honoré; McDowell, Christina (Canadian Journal of Counselling and Psychotherapy, 2012)
Peer counselling has become a common innovative feature in many schoolcounselling programs. The authors have developed a model which combines peercounselling principles for use with a computer-assisted career counselling program.This student orientated model outlines a two phase training program and providespractical guidelines for implementation using the CHOICES system. The student peercounsellors are trained in communication skills to facilitate self-exploration, valuesclarification and decision making while operating within their own social network.The practicum sessions provide an opportunity to focus specifically on career counsellingissues, to gain experience and familiarity with both the CHOICES system andcurrent literature, and to achieve competency with life/career planning skills. Thismodel is designed to assist the school counsellor in implementing CHOICES into anoverall career counselling program.